مقروئية الكتاب شبه المدرسي للغة العربية عند تلاميذ السنة الخامسة من التعليم الإبتدائي-بعض ابتدائيات بلدية الوادي أنموذجا - حرزولي, كنيوة, اسماء أسماء; ديدي, مروة (University of El-oued, 2022)
تهدف الدراسة إلى البحث في إحدى الوسائل التعليمية التي أضحت تلازم التلاميذ, والمتمثلة في الكتب شبه المدرسية للغة العربية, من خلال البحث والتركيز على مدى مقروئيتها عند تلاميذ السنة الخامسة من التعليم الابتدائي, ولتحديد جدوى ذلك التفاعل قمنا _ بعد التنظير لمقتضيات البحث _ بدراسة وصفية تحليلية لعينة من الكتب شبه المدرسية _كتاب سلسلة التحدي في اللغة العربية أنموذجا_ من حيث الشكل والمضمون, والمتن التعليمي لهذا الكتاب وعلاقته بالكتاب المدرسي, ودعّمنا التحليل بدراسة ميدانية شملت عينة من معلمي (أساتذة) اللغة العربية, وعينة من متعلمي (تلاميذ) السنة الخامسة, والذين أبانوا بآرائهم الجادة عن مقروئية هذه الكتب بشكل مكثف وملفت, نظرا لميزاته التعليمية, مما استوجب اقتراح الأساتذة لأساليب قصد الاستفادة من الكتب شبه المدرسية في تعليم اللغة العربية. The study aims to research one of the educational means that has become associated with students, which is the semi-school books of the Arabic language, through research and focus on the extent of their readability among students of the fifth year of primary education, and to determine the feasibility of that interaction, we, after theorizing for the requirements of the research, conducted a descriptive and analytical study For a sample of semi-school books - The Challenge Series book in the Arabic language as a model - in terms of form and content, The educational body of this book and its relationship to the textbook, and we supported the analysis with a field study that included a sample of teachers (teachers) of the Arabic language, and a sample of learners (students) of the fifth year, who expressed their serious opinions about the readability of these books intensively and strikingly, due to their educational features, which necessitated a proposal Teachers for methods in order to benefit from semi-school books in teaching Arabic.
Keywords: الكتاب المدرسي, الكتاب شبه المدرسي, المقروئية.; textbook, semi-textbook, readability.